NUMERICAL INVESTIGATION OF REAR WINDSHIELD ANGLE AND REYNOLDS NUMBER EFFECTS ON THE AERODYNAMIC PERFORMANCE OF A SALOON CAR - Dwi Tarti; Ika Nurjannah; Herman Sasongko (Otopro, 2026)
This study examined how rear windshield angle and body geometry affect the aerodynamic behavior of a saloon car model using numerical simulations. Rear windshield angles of 45°, 60°, 75°, and 90° were considered for two configurations—sharp and rounded rear corners— whereas the front windshield angle was kept constant at 30% to allow a consistent comparison. Simulations were conducted at two Reynolds numbers, 6.5×10⁶ and 11.8×10⁶, corresponding to inlet velocities of 22.2m/s and 40m/s. The simulations were performed using ANSYS Fluent 2024, focusing on the flow behavior along the upper and lower surfaces, as well as the resulting drag and lift characteristics. The results showed that increasing the rear windshield angle generally led to higher drag, mainly due to the expansion of the wake region behind the vehicle. Models with rounded corners consistently performed better than sharp-edged ones, producing lower drag and more stable flow behavior. The lowest drag coefficient (CD=0.556) was found for the rounded configuration at a 45° rear windshield angle, whereas the highest value (CD=0.8147) appeared in the sharp configuration at 90°. From the flow visualization, it can be seen that the sharp edges create stronger adverse pressure gradients, which trigger earlier separation and lead to a larger wake. In contrast, rounded corners helped the flow to recover more smoothly and delayed separation. Overall, these findings emphasize the role of the rear windshield angle and body geometry in improving aerodynamic efficiency and minimizing energy losses.